Psychosocial stress and asthma morbidity - Yonas, Michael A. (2012)
PURPOSE OF REVIEW: The objective of this review is to provide an overview and discussion of recent epidemiologic and mechanistic studies of stress in relation to asthma incidence and morbidity. RECENT FINDINGS: Recent findings suggest that stress, whether at the individual- (i.e., epigenetics, perceived stress), family- (i.e., prenatal maternal stress, early life exposure or intimate partner violence) or community- (i.e.., neighborhood violence; neighborhood disadvantage) level influences asthma and asthma morbidity. Key recent findings regarding how psychosocial stress may influence asthma through Post Traumatic Stress Disorder (PTSD), pre-and post-natal maternal/caregiver stress, and community violence and deprivation are highlighted. SUMMARY: New research illustrates the need to further examine, characterize and address the influence of social and environmental factors (i.e., psychological stress) on asthma. Further research and innovative methodologies are needed to characterize the relationship and pathways associated with stress at multiple levels to more fully understand and address asthma morbidity, and to design potential interventions, especially to address persistent disparities in asthma in ethnic minorities and economically disadvantaged communities.